TECHNOLOGY ACCEPTANCE MODEL (TAM) ANALYSIS OF THE USE OF OVO APPLICATION IN F&B SERVICE INDUSTRY IN INDONESIA - Reyner Ditya Susanto; Raynald Tjandinegara; Vido Iskandar; Endo Wijaya Kartika (Bahasa Indonesia, 2021)
This study aims to determine factors that influence user’s behavioral intention in using OVO as payment method in F&B industry in generation Z. The result of this research shows that Perceived usefulness will have direct influence in increasing user’s intention to use OVO and indirect influence by increasing user’s attitude which will strengthen the connection between perceived usefulness and behavioral intention. Perceived ease of use is proven to be not significant in increasing user’s intention directly. But perceived ease of use will increase user’s positive attitude first toward the usage of OVO which will eventually increase people’s intention toward using OVO as payment method in F&B industry